2005
DOI: 10.1152/ajpgi.00050.2005
|View full text |Cite
|
Sign up to set email alerts
|

Volume-activated chloride currents in interstitial cells of Cajal

Abstract: cells of Cajal (ICC) undergo marked morphological changes on contraction of the musculature, making it essential to understand properties of mechanosensitive ion channels. The whole cell patch-clamp technique was used to identify and to characterize volume-activated Cl Ϫ currents in ICC cultured through the explant technique. Hypotonic solutions (Ϸ210 mosM) activated an outwardly rectifying current, which reversed near the equilibrium potential for Cl Ϫ . Time-dependent inactivation occurred only at pulse pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Nevertheless, they show some common features such as the dependence on intracellular ATP, outward rectification, time-dependent inactivation at positive potentials, and the fact that I − is more permeable than Cl − [28]. Although poorly selective, a wide range of compounds can block I Cl,swell at micromolar concentrations including: calyx-arenes, glibenclamide, tamoxifen, 4-acetamido−4′-isothiocyanostilbene-2,2′-disulphonic acid (SITS), 4,4′-diisothiocyanatostilbene-2,2′-disulfonic acid (DIDS), 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), anthracene-9-carboxylic acid (9-AC), niflumic acid, and purinergic antagonists [1,16,24,35,41,47]. I Cl,swell can also be modulated by PKA, PKC, PKT, and MAP kinases, depending on the cell type and experimental conditions [9,46,53].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, they show some common features such as the dependence on intracellular ATP, outward rectification, time-dependent inactivation at positive potentials, and the fact that I − is more permeable than Cl − [28]. Although poorly selective, a wide range of compounds can block I Cl,swell at micromolar concentrations including: calyx-arenes, glibenclamide, tamoxifen, 4-acetamido−4′-isothiocyanostilbene-2,2′-disulphonic acid (SITS), 4,4′-diisothiocyanatostilbene-2,2′-disulfonic acid (DIDS), 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), anthracene-9-carboxylic acid (9-AC), niflumic acid, and purinergic antagonists [1,16,24,35,41,47]. I Cl,swell can also be modulated by PKA, PKC, PKT, and MAP kinases, depending on the cell type and experimental conditions [9,46,53].…”
Section: Introductionmentioning
confidence: 99%
“…For several years, Ca 2ϩ -activated Cl Ϫ currents have been recorded from interstitial cells of Cajal (ICCs) (12,13,16,24,25,47,48). In particular, anoctamin 1 (Ano1), also known as TMEM16A or DOG1, is a selective marker of ICCs in the GI tract (9).…”
mentioning
confidence: 99%
“…On the other hand, ICC pacemaker activities are mainly due to periodic activations of non-selective cation channels (NSCCs) [15,16] or Cl - channels [17,18,19,20,21,22], and TRPM7 and ANO1 channels are the main candidates for the NSCC and Cl - channels responsible for the pacemaker activity in ICC [18,25,26,30]. Therefore, TRPM7 and ANO1 modulators are potential targets for the treatment of GI motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence indicates that endogenous agents, such as, neurotransmitters, hormones, and paracrine substances, modulate GI tract motility by influencing ICC [14]. It has been shown that the pacemaker activities of ICC in the murine small intestine are mainly due to periodic activations of nonselective cation channels (NSCCs) [15,16] or Cl - channels [17,18,19,20,21,22]. Kim et al [16] suggested that transient receptor potential melastatin (TRPM) 7 is required for ICC pacemaker activity in the murine small intestine, and a Ca 2+ -activated Cl - channel (CaCC) is involved in slow wave generation in ICC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation